EXPLORING THE VALUE OF PEER FEEDBACK IN AN ESL WRITING CLASS - Noryani Neni Ahmad Jamain; Sazuliana Sanif; Asliaty Atim, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The study of peer feedback in enhancing learning has been evident in the literature. Notably, its value has left marked improvement in language learning. Although there have been critics about its significance, it undeniably has significant traces in learning. This study looked into the practice of peer feedback implemented during a writing course program that took four weeks to complete. The study aimed to explore learners' perceptions about the practice and the challenges they faced while engaging in peer feedback practices. The study adopted a qualitative approach in which data were obtained from 10 participants' reflective writings collected at the completion of the writing programme. The results indicated that learners found they had a positive experience with the practice because the feedback from peers complemented feedback received from the teacher. Furthermore, the practice provided more opportunities for class interaction between peers, thus making English class more meaningful. However, setbacks like time constraints and students' acceptance of peer comments are challenges that need to be addressed in the future. Nevertheless, peer feedback in ESL classrooms, particularly in writing class, is worth considering in enhancing English language learning experience.